High molecular weight hyper-branched PCL-based thermogelling vitreous endotamponades. (January 2022) - Lin, Qianyu; Liu, Zengping; Wong, Daniel S.L.; Lim, Chen Chuan; Liu, Connie K.; Guo, Liangfeng; Zhao, Xinxin; Boo, Yi Jian; Wong, Joey H.M.; Tan, Rebekah P.T.; Xue, Kun; Lim, Jason Y.C.; et al.
Abstract: Vitreous endotamponades play essential roles in facilitating retina recovery following vitreoretinal surgery, yet existing clinically standards are suboptimal as they can cause elevated intra-ocular pressure, temporary loss of vision, and cataracts while also requiring prolonged face-down positioning and removal surgery. These drawbacks have spurred the development of next-generation vitreous endotamponades, of which supramolecular hydrogels capable of in-situ gelation have emerged as top contenders. Herein, we demonstrate thermogels formed from hyper-branched amphiphilic copolymers as effective transparent and biodegradable vitreous endotamponades for the first time. These hyper-branched copolymers are synthesised via polyaddition of polyethylene glycol, polypropylene glycol, poly(ε-caprolactone)-diol, and glycerol (branch inducing moiety) with hexamethylene diisocyanate. The hyper-branched thermogels are injected as sols and undergo spontaneous gelation when warmed to physiological temperatures in rabbit eyes. We found that polymers with an optimal degree of hyper-branching showed excellent biocompatibility and was able to maintain retinal function with minimal atrophy and inflammation, even at absolute molecular weights high enough to cause undesirable in-vivo effects for their linear counterparts. The hyper-branched thermogel is cleared naturally from the vitreous through surface hydrogel erosion and negates surgical removal. Our findings expand the scope of polymer architectures suitable for in-vivo intraocular therapeutic applications beyond linear constructs.